Short-term effects of particulate matter constituents on daily hospitalizations and mortality in five South-European cities: Results from the MED-PARTICLES project. (February 2015) - Basagaña, Xavier; Jacquemin, Bénédicte; Karanasiou, Angeliki; Ostro, Bart; Querol, Xavier; Agis, David; Alessandrini, Ester; Alguacil, Juan; Artiñano, Begoña; Catrambone, Maria; de la Rosa, Jesús D.; Díaz, Julio; et al.
Abstract: Background: Few recent studies examined acute effects on health of individual chemical species in the particulate matter (PM) mixture, and most of them have been conducted in North America. Studies in Southern Europe are scarce. The aim of this study is to examine the relationship between particulate matter constituents and daily hospital admissions and mortality in five cities in Southern Europe. Methods: The study included five cities in Southern Europe, three cities in Spain: Barcelona (2003–2010), Madrid (2007–2008) and Huelva (2003–2010); and two cities in Italy: Rome (2005–2007) and Bologna (2011–2013). A case-crossover design was used to link cardiovascular and respiratory hospital admissions and total, cardiovascular and respiratory mortality with a pre-defined list of 16 PM10 and PM2.5 constituents. Lags 0 to 2 were examined. City-specific results were combined by random-effects meta-analysis. Results: Most of the elements studied, namely EC, SO4 2 −, SiO2, Ca, Fe, Zn, Cu, Ti, Mn, V and Ni, showed increased percent changes in cardiovascular and/or respiratory hospitalizations, mainly at lags 0 and 1. The percent increase by one interquartile range (IQR) change ranged from 0.69% to 3.29%. After adjustment for total PM levels, only associations for Mn, Zn and Ni remained significant. For mortality, although positive associations were identified (Fe and Ti for total mortality; EC and Mg for cardiovascular mortality; and NO3 − for respiratory mortality) the patterns were less clear. Conclusions: The associations found in this study reflect that several PM constituents, originating from different sources, may drive previously reported results between PM and hospital admissions in the Mediterranean area. Highlights: Little is known about which specific PM constituents are more harmful. We investigate the association between concentrations of PM constituents and health. Mortality and hospitalizations were associated with several PM constituents. The highest effects were observed for elemental carbon and nickel.